Understanding Sectoral Shifts In Labour Market And Wage Inequality In India: With Special Reference To Economic Reforms (Journal of Namibian Studies : History Politics Culture, 2022)
The inception of economic reforms in 1991 was the starting point towards integrating the Indian economy with the global economy. India opens its eyes to the reality and realizes the vast potential of a market economy. Economic reform leads to gradual integration of economies through free movement of goods, services and capital. The idea that economic reform can create "losers" as well as "winners" has, after an initial resistance, begun to attract the attention of economic researchers and of policy makers at both the national and multilateral levels. This paper aims to explore two key aspects of the impact of economic reform on the labor market i.e. shift in labor market and wage inequality. The period of study is 1971-2021. Indian occupational structure was changed in the post reform period. The study finds that after economic reforms the share of employment in agriculture sector decline. The paper observed an increasing trend of employment in industrial sector especially in construction sector. Again employment in service sector also shows a rising trend. Wage disparities between skilled and unskilled labor have increased as a result of economic restructuring.